(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To identify and analyze factors associated with the severity of community-acquired pneumonia among children aged 2-60 months at Ha Quang district Medical Center, Cao Bang province, Vietnam. Method: A cross-sectional descriptive study. Results: The study of 216 patients showed that the 2-12 month age group had a higher rate of severe pneumonia compared to the 12-60 month age group. Children with anemia, rickets, or malnutrition also had higher rates of severe pneumonia than those without these conditions, and the differences were statistically significant with p-values of 0.012; 0.031, and 0.021, respectively. However, logistic regression analysis, only two factors remained independently associated with the severity of pneumonia: younger age (2-12 months) and living in a household with smokers. Specifically, children aged 2-12 months had 2.29 times higher odds of developing severe pneumonia compared with those aged 12-60 months (OR = 2.290; p = 0.012), while children living with smokers had 2.10 times higher odds of severe pneumonia than those not exposed to tobacco smoke (OR = 2.105; p = 0.031). Conclusion: The study highlights several key factors influencing the severity of community-acquired pneumonia in young children, age under 12 months, exposure to household cigarette smoke.